Antioxidant activity of three different Serbian floral honeys - Savatović Slađana M.; Dimitrijević Dejan J.; Đilas Sonja M.; Čanadanović-Brunet Jasna M.; Ćetković Gordana S.; Tumbas Vesna T.; Štajner Dubravka I. (Acta Periodica Technologica, 2011)
In this study, three Serbian honey samples (Acacia, Linden and "Homoljski med") were analyzed to determine their total phenolic, flavonoid and antioxidant content, as well as their in vitro antioxidant activity. The antioxidant activity of honeys was examined by different tests, including the reducing power and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. In addition, correlations between the antioxidant activity and total phenolic, as well as flavonoid content were also sought. The highest content of total phenolics (27.44 mg/100 g), flavonoids (9.78 mg/100 g), reducing power and DPPH free radical scavenging activity were obtained in the case of Linden honey. The EC50 values of the Linden honey, determined based on the reducing power and DPPH radical scavenging activity, were 24.17 mg/ml and 51.34 mg/ml, respectively. Also, the antioxidant content was highest for Linden honey, and it valued 5.45 mg QEAC/100 g (expressed as mg of quercetin equivalent antioxidant content - QEAC per 100 g of honey) and 7.82 mg AEAC/100 g (expressed as mg of ascorbic acid equivalent antioxidant content - AEAC per 100 g of honey). Also, a linear correlation was observed between the antioxidant activity and total phenolics, as well as total flavonoids.